Functional genomics and evolution of photosynthetic systems - Vermaas, Wim; Burnap, Robert (Advances in Photosynthesis and Respiration, 2012)
Recent advances in the genomics of photosynthetic organisms, coupled with increased understanding photosynthetic mechanisms, provides new perspectives on the function and evolution of the photosynthetic mechanisms.  Correspondingly, a central theme of the book is the application of comparative methods that exploit the explosive growth in biological sequence data to inform our understanding of the operation and evolution of photosynthetic mechanisms.  Since many of the relevant structures and pathways are increasingly well-understood, a goal is to integrate the genomics with this structural and mechanistic knowledge.